Ptch2/Gas1 and Ptch1/Boc differentially regulate Hedgehog signalling in murine primordial germ cell migration - Yeonjoo Kim (Nature Portfolio, 2020)
How co-receptors Gas1 and Boc interact with Ptch1/2 receptors and regulate Hh signalling is unclear. Here, the authors demonstrate that the spatiotemporal expression of Gas1 and Boc determines how Hh signalling affects the dynamic migration of murine primordial germ cells.